Knowledge and practice of breastfeeding among lactating mothers in AIIMS, Bhubaneswar - A hospital-based cross-sectional study - Mythry Ravichandran; Swayam P. Parida; Arvind K. Singh; Abhisek K. Mishra; Kumbha Gopi (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: 44% of infants under 6 months of age worldwide are only adequately breastfed. It is also found that only 41.6% of women breastfeed their child within one hour of birth and less than 50% of women continue breastfeeding up to 2 years. This study was conducted to assess the prevalence of early initiation of breastfeeding practice, to explore the knowledge and practices about breastfeeding among lactating mothers, and to find the effect of breastfeeding on the nutritional status of the child. MATERIALS AND METHODS: A hospital-based study was conducted among 160 lactating mothers of infants below six months of age presenting to the immunization clinic at AIIMS Bhubaneswar. A semi-structured questionnaire based on the CDC breastfeeding questionnaire was administered to assess the knowledge and practice. The nutritional status of the infant was assessed by plotting the weight for age and length for age of the infant in the WHO growth charts. RESULTS: 102 (75%) of mothers had initiated breastfeeding within the first hour of delivery. Adequate knowledge and practice of breastfeeding was present only in 4 (2.5%) and 3 (1.9%), respectively. It was found that 13.75% of women were using formula feed. The prevalence of underweight and less than normal length was 40% (n = 64) and 34.37% (n = 55) among infants, respectively. CONCLUSION: This study emphasizes the importance of awareness among lactating mothers about the hindmilk, appropriate practice, and to find its effect on the nourishment of the children.